2006
DOI: 10.1037/1089-2699.10.1.43
|View full text |Cite
|
Sign up to set email alerts
|

From leadership to parenthood: The applicability of leadership styles to parenting styles.

Abstract: Lewin's (1948) three styles of leadership and group dynamics provided the basis for Dreikurs' (1995) formulation concerning parental styles. Baumrind's (1971) later parenting typology, also based on Lewin, focused on parent-child dyads, whereas Dreikurs referred to the total family patterning with parents as group leaders. The present article measured young adults' perceived parenting values that occurred in childhood and corresponded to Dreikurs' and Lewin's leadership styles: autocratic, democratic, and lais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…On a similar note, parental value measures were altered in order to increase construct validity. The original 15‐item measure was found to have a slightly different factor structure than originally hypothesized for students in the United States (see Ferguson et al., ). The 40‐item measure was constructed in order to better capture the parenting styles across cultures in the 21st century.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…On a similar note, parental value measures were altered in order to increase construct validity. The original 15‐item measure was found to have a slightly different factor structure than originally hypothesized for students in the United States (see Ferguson et al., ). The 40‐item measure was constructed in order to better capture the parenting styles across cultures in the 21st century.…”
Section: Discussionmentioning
confidence: 95%
“…Following the TR task, participants received the Parental Values (PV) scale that asked for ratings on 15 items as described by Ferguson et al. (). The earlier report on the scale (Ferguson et al., ) concluded that the three significant factors were not the same as those reported by Lewin et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations